Navigating end-of-life decision making: a thematic analysis of Uchinanchu American older adult’s information behaviour - Kristina Shiroma (Information Research: An International Electronic Journal)
Introduction. End-of-life (EOL) involves complex decision-making, influenced by how individuals seek, share, and process information. This study examines the EOL decision-making information behavior of older Uchinanchu (Okinawan) Americans, an underrepresented ethnic minority.